Pendampingan Praktik Wudhu dalam Pemahaman Taharah di SMA Kapuas Pontianak - Kudsiyeh; Husni, Muhammad (Belalek, 2025)
In the context of Islamic religious education, a deep understanding of purification rituals, particularly ablution (wudu), is essential as it serves as a primary requirement for performing prayer (salat). However, many people, especially children, often face difficulties in correctly understanding the procedures of wudu due to conventional methods of instruction, which rely heavily on books that are less engaging and interactive. Therefore, the implementation of innovative and participatory programs becomes a crucial solution to enhance the community’s comprehension and skills in performing worship properly. This community service activity aims to provide children with a better understanding of wudu practices to improve their religious quality at SMA Kapuas Pontianak, involving 40 students. The PKM approach applied was direct practice. The results of the wudu program at SMA Kapuas Pontianak indicate that this activity has had a positive impact on the students’ religious quality. By strengthening their understanding of the importance of wudu, the students have become more disciplined in performing worship. This program not only reinforces spiritual aspects but also contributes to shaping better character among the younger generation, which is highly significant in the context of religious education.